Internationalization and creation of new products and processes in the Mexican manufacturing industry - Meza González, Liliana (Estudios Económicos de El Colegio de México, 2016)
This paper tries to understand the relationship between internationalization and the generation of new products and processes in a developing country, using data from 2285 Mexican manufacturing firms and for the 2008-2009 period. Through an econometric analysis, this paper contributes to the literature and concludes that, after controlling for the size of the firm, its innovative effort and the concentration of the market power in the industry, being an exporter promotes the generation of new processes and of innovations for the world; FDI also promotes innovation for the world; being an importer does not affect the innovative outcomes of the firm, while outsourcing inhibits the generation of both new products and processes, and the innovation for the world.